Influence of Grain Size on the Agglomeration and Quality of Fine Couscous Derived from Decorticated White Sorghum Bicolor L. - Mahieddine, Cherifa; Nadjemi, Boubekeur (The North African Journal of Food and Nutrition Research, 2025)
Aims: This study sought to estimate the effect of white Sorghum bicolor L. grain size and the decortication process on the production yield, physicochemical characteristics, cooking properties, color, and sensory quality of sorghum-based couscous. Methods: White Sorghum bicolor L. grains originating from the same crop batch were initially separated into three distinct fractions based on their size. These fractionated grains were subsequently decorticated and milled to obtain sorghum semolina, which was then agglomerated to produce three respected homemade couscous samples. For comparative analysis, commercial ready-made durum semolina was employed to prepare a control couscous sample. All samples, including the control, were meticulously evaluated for their proximate composition (specifically protein, starch, and dietary fiber content), cooking properties, color indices, and overall sensory attributes. Results: The three homemade couscous samples of sorghum were produced with a high yield, ranging from 88.42 to 90.27%, significantly surpassing the control yield of 82.30 %. The nutritional composition of the sorghum samples—namely the protein, starch and dietary fiber contents was both high and showed significant variations dependent on the initial grain size. The protein, starch, and dietary fiber contents in the sorghum couscous samples ranged from 11.45 to 14.67%, 60.18 to 75.51%, and 2.61–10.55%, respectively. Furthermore, the sorghum couscous exhibited a noticeably darker color compared to the control. Sorghum couscous samples A and B exhibited favorable cooking quality, although they required a prolonged cooking time. They also achieved moderate overall acceptability scores for appearance and color. Conversely, sorghum couscous C was characterized by poor cooking loss and received lower sensory attribute scores. Conclusions: The findings definitively confirm the significant influence of grain size on both the semolina agglomeration process and the ultimate quality characteristics of the sorghum couscous. Moreover, the decortication process was associated with the production yield, particle size distribution, and color profile of the final sorghum couscous product. Keywords: White Sorghum bicolor; Grain Size; Couscous; Physicochemical Properties; Nutrient Content; Food quality.